Modulation of social space by dopamine in Drosophila melanogaster, but no effect on the avoidance of the Drosophila stress odorant - Fernandez, Robert W. (Biol Lett, 2017)
Appropriate response to others is necessary for social interactions. Yet little is known about how neurotransmitters regulate attractive and repulsive social cues. Using genetic and pharmacological manipulations in Drosophila melanogaster, we show that dopamine is contributing the response to others in a social group, specifically, social spacing, but not the avoidance of odours released by stressed flies (dSO). Interestingly, this dopamine-mediated behaviour is prominent only in the day-time, and its effect varies depending on tissue, sex and type of manipulation. Furthermore, alteration of dopamine levels has no effect on dSO avoidance regardless of sex, which suggests that a different neurotransmitter regulates this response.